A METAPHYSICAL UNDERSTANDING OF THE HUMAN PERSON AND THE PHILOSOPHY OF UTUISM. - Waitherero, Njuguna (2019)
This article seeks to understand the metaphysical nature of human person that helps in understanding the human behavior. This behavior is dictated by the existence of Utu in the human person. The paper relates human behavior with utuism and explains the reasons why human person behave in a particular way.
Keywords: Human person; Utuism; and utu